Stroke etiology by occlusion site – data from the PRAGUE 16 study. (25th November 2020) - Vavrova, J; Koznar, B; Peisker, T; Vasko, P; Rohac, F; Sulzenko, J; Kroupa, J; Stetkarova, I; Mengozzi, L; Widimsky, P
Abstract: Background: Catheter-based thrombectomy (CBT) is the most effective treatment for acute ischemic stroke. Endovascular treatment program - Prague 16 was established in tertiary university hospital in 2012 as result of close cooperation among cardiologists, neurologists and radiologists. The aim of this substudy is to analyze relationship between stroke localization and its etiology. Methods: Single center, prospective registry of consecutive patients (pts) treated by CBT for acute ischemic stroke. Total of 214 pts (median 70 ys, range 21–92 ys, men 53.3%) were enrolled between 2012 and 2018. During hospitalization and subsequent 3-months follow-up, all pts were carefully examined (at least 48 hours ECG monitoring, CT angiography, carotid arteries sonography, transthoracal/ transoesofageal echocardiography) to determine the most likely stroke etiology. Results: Relative frequency of strokes based on occlusion site and their etiology is shown in table below. In half of all strokes (50.9%), stroke etiology was assumed to be cardioembolic, mostly due to atrial fibrillation (89.0%). Isolated middle cerebral artery (MCA) occlusion and T-type strokes were mostly caused by cardioembolism (66.3% and 58.9%), unlike vertebrobasilar (VB) strokes, isolated internal carotid artery (ICA) occlusion/tight stenosis and tandem occlusion strokes were mostly atherotrombogenic (53.8%, 44.8% and 55.6%). Conclusions: The majority of strokes with MCA and T-type occlusion was caused by cardioembolization, mostly due to atrial fibrillation. ICA occlusion, tandem occlusion and VB occlusion strokes were mostly caused by atherotrombosis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Charles University Research Project Progress Q35